Digital Storybooks on Young Learners’ Reading Skills: A Systematic Literature Review - Ni Putu Yunda Kirana; Ni Wayan Surya Mahayanti; Ni Luh Putu Era Adnyayanti (English Education Department STKIP Agama Hindu Singaraja, 2026)
This study investigates the effectiveness of digital storybooks in improving young learners’ reading skills, addressing the persistent challenges of low reading comprehension, limited vocabulary, and poor engagement in early literacy classrooms. With children increasingly growing up in digitally rich environments, traditional print-based instruction often fails to capture their attention. By creating an urgent need for instructional approaches that align with their digital experiences while supporting essential literacy skills. A Systematic Literature Review guided by the PRISMA framework was conducted. Ten empirical studies published between 2018 and 2024 were selected based on clear inclusion and exclusion criteria. These studies were analyzed to identify how digital storybooks influence reading comprehension, vocabulary development, story sequencing, and engagement. The findings show that digital storybooks significantly enhance reading comprehension, vocabulary acquisition, and engagement. Multimodal features such as text highlighting, visual cues, and audio narration help learners process information more effectively and remain motivated. Teacher guidance and well-designed materials further improve outcomes. Overall, this study underscores that urgent need to integrate digital storybooks into early literacy instruction. It provides evidence-based guidance for educators and highlights directions for future research, including investigating long-term impacts and broader classroom applications.